Basque camp : inter-departmental correspondence - Harries, E. P.
039-0105-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: E.P.H Department To: WMC Date: May 31st SUBJECT. Basque Camp Mr Tewson & I visited the camp yesterday & found that a big improvement has been made. Loud speakers now control the camp, health is good, every child is getting enough food & a cinema tent is being erected. We saw the town clerk of Eastleigh & he agreed that things were very much better, but urged as speedy an evacuation as possible. The Commandant of the Girl Guides camp said the same thing, they have already changed [...]t sites once. Wilfrid Roberts hopes to be able to send 200 children a day clearing the camp in 3 weeks. I am trying to get Dr [Crails?] of the Ministry of Health to give me an unofficial interview before the meeting this afternoon. E.P.H. 292/946/39/105